2019
DOI: 10.1016/j.ijpe.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Towards a contingency theory perspective of quality management in enabling strategic alignment

Abstract: The aim of this paper is to explore the role of Quality Management (QM) theory and practice using a contingency theory perspective. The study is grounded in the role of QM in improving strategic alignment within Small and Medium Sized Enterprises (SMEs) using Contingency Theory rather than adopting best practice approaches. An inductive theory building research methodology was used involving multiple case analyses of five SMEs, involving repeat 2 interviews (n=45), focus groups (n=5) and document analysis. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 53 publications
3
110
0
7
Order By: Relevance
“…The effectiveness of the MACS depends on whether its design can be matched with the surrounding environment, technological factors, company size, and company strategy (Fisher, 1995;Chenhall, 2003). Chenhall (2003), McAdam et al (2019, Zhang et al (2017) and others have shown that contingency theory is appropriate for establishing an effective MACS, and an effective MACS will have a positive impact on the firms' performance. Hence, contingency theory is generally suitable for this study.…”
Section: Theoretical Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…The effectiveness of the MACS depends on whether its design can be matched with the surrounding environment, technological factors, company size, and company strategy (Fisher, 1995;Chenhall, 2003). Chenhall (2003), McAdam et al (2019, Zhang et al (2017) and others have shown that contingency theory is appropriate for establishing an effective MACS, and an effective MACS will have a positive impact on the firms' performance. Hence, contingency theory is generally suitable for this study.…”
Section: Theoretical Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Contingency theory holds that organizational effectiveness is generated by fitting or matching organizational characteristics with contingency factors that reflect organizational situations (McAdam, Miller, & McSorley, 2019).…”
Section: Contingency Theorymentioning
confidence: 99%
“…The paradigm revolution of significant market works and structures, population dynamics, perpetuated organizations and resource dependence (Carrol, ; McAdam, Miller, & McSorley, ) deposed the contingency theory which hypothesized that environmental fits were correlated with performance. Dhir and Dhir () stressed that these works led to several strands of research which are still prevalent and have greatly contributed to organizational learning.…”
Section: Late 1930s—early 1980smentioning
confidence: 99%